Strength enhancement due to FRP confinement for coarse aggregate-free concretes. (15th February 2023) - Jiang, Cheng
Highlights: The similarity of strength enhancement for FRP-confined UHPC and ECC is caused by the inexistence of coarse aggregates. All the coarse aggregate-free concretes have similar strength enhancement effects due to FRP confinement. A general model for strength enhancement due to FRP confinement is proposed for all coarse aggregate-free concretes. This paper can guide future research on confinement for next-generation coarse aggregate-free cementitious materials. Abstract: Concrete strength can be effectively enhanced by external fiber reinforced polymer (FRP) confinement. However, it is found from the literature that the strength enhancement coefficient ( k 1 ) varies significantly, especially for different types of concrete. This paper presents an in-depth investigation of the variety of strength enhancement coefficients with concrete types. First, two state-of-the-art databases for FRP-confined UHPC and FRP-confined ECC specimens are constructed in this paper. From analyzing the databases, although the mechanical performances and components are different for UHPC and ECC, nonetheless, their strength enhancement coefficients are quite similar ( k 1  = 2.27 and 2.01, respectively). With the validation by an experimental program on FRP-confined mortar specimens, it can be concluded that the similarity of strength enhancement coefficients for FRP-confined UHPC, ECC, and mortar, which are much lower than that for normal concrete, is caused by the lack of coarse aggregates. The reasons are discussed and well explained by a simplified experiment with steel balls and shear-friction mechanism. Based on the research, this paper proposed a unified strength enhancement coefficient, i.e., 2.13, for all coarse aggregate-free concretes. As the existence of coarse aggregates is found to be the main governing factor for the strength enhancement coefficient, this paper provides a fundamental basis for future research on confinement for next-generation coarse aggregate-free cementitious materials, such as lunarcrete and 3D-printed concrete.